Adsorption of metribuzin herbicide on raw maghnite and acid-treated maghnite in aqueous solutions - A. Bettayeb; B.A. Reguig; Y. Mouchaal; M.A. Yahiaoui; M.M. Chehimi; Y. Berredjem (Desalination and Water Treatment, 2018)
This study aims to examine the potentialities of raw maghnite and acid-activated maghnite (raw- Mag and Mag-H+) for Metribuzin herbicide removal from aqueous solutions. Raw-Mag and Mag-H+ were characterized using various analytical techniques such as NMR, BET, FTIR, FRX, ATD and SEM. The effect of various operating parameters such as contact time, Metribuzin concentration, pH, and adsorbent dose were investigated using raw-Mag and H-Mag in batch adsorption system. The results showed that the maximum adsorption capacity was 70.1 and 55.6 mg/g for raw-Mag and Mag-H+ respectively at pH 2.5, initial Metribuzin concentration of 20 mg/L, adsorbent raw-M and Mag-H+ dosage of 0.5 and 0.2 g/L . The adsorption of Metribuzin herbicide was important in acidic medium for both adsorbents. Furthermore, the adsorption uptake was found to be increased with increase initial concentration. The equilibrium adsorption data were well described by Freundlich and Langmuir isotherms. The kinetic studies showed that the experimental data was best describing by pseudo second order model. The Mag-H+ had above 30% adsorption uptake capacity after four regeneration cycles, this was higher than Raw-Mag. It was observed from the values of thermo- dynamics parameters such us Gibbs free energy (∆G°), enthalpy (∆H°), and entropy (∆S°), that the nature of adsorption is spontaneous